Desenvolvimento de procedimentos eletroanalíticos para a determinação de fármacos em formulações farmacêuticas e fluidos biológicos empregando sensores à base de carbon black - Silva, Laís Pereira (2019)
In this work, voltammetric methods for determination of losartan potassium and ketoconazole using an electrode modified with carbon black were developed. Originally, a sensor was constructed with carbon black, chitosan and epichlorohydrin. Than, it was used for the determination of losartan. The electrochemical behavior of the losartan was studied with cyclic voltammetry in 0.2 mol L−1 phosphate buffer solution (pH 3.0), which presented an irreversible oxidation peak at a potential of 1.28 V. The square wave voltammetry technique was selected for the quantification of losartan in commercial pharmaceutical formulations and synthetic biological samples. The following parameters were evaluated: frequency, pulse amplitude and step potential. A linear response was observed in the concentration range from 4.97 × 10−6 to 4.76 × 10−5 mol L−1 represented by the linear regression equation: Ip (μA) = − 6.04 × 10−8 + 0.122 [LOS] (μmol L−1); r = 0.990 and with a limit of detection of 4.79 × 10−7 mol L−1. The method developed was successfully applied for the determination of losartan in pharmaceutical formulations and the comparison of these results to UV-visible spectrophotometry determination, do not presented significant difference at confidence level of 95% using a t-test student. In addition, the determination of losartan was performed in samples of synthetic biological fluids, with satisfactory results. The electrochemical behavior of the ketoconazole was performed through cyclic voltammetry using a glassy carbon electrode modified with carbon black, chitosan and gold nanoparticles in 0.2 mol L−1 phosphate buffer (pH 10). An irreversible oxidation peak was observed at 0.65 V. The ketoconazole determination was developed using square wave voltammetry under optimized conditions. The obtained analytical curve was linear in the concentrations range of ketoconazole, from 1.00 × 10−7 to 2.90 × 10−6 mol L−1, according to the linear regression equation: Ip (μA) = −1, 8 × 10−8 + 3.6 [CTO] (μmol L−1); r = 0.999, with a limit of detection of 4.43 × 10−9 mol L−1. In addition, the voltammetric procedures were successfully applied in the ketoconazole determination in pharmaceutical formulations and synthetic biological samples with satisfactory results.